Behavioral and Personality Changes as the First Manifestation of Spinocerebellar Ataxia Type 2 - Davide Vilella; Daniele Urso; Agnese Valguarnera; Giuseppe Volpe; Maria Accadia; Chiara Zecca; Alessandra Vitulli; Roberto De Blasi; Alessandro Bertolino; Giancarlo Logroscino (The Cerebellum, 2026)

Can economic benefits foster sustainability? A preliminary study on the transition from polystyrene to polypropylene boxes in selected Italian fisheries - Loretta Malvarosa; Paolo Accadia; Maria Cozzolino; Carlo Paolucci; Rosaria Felicita Sabatella (Frontiers in Marine Science, 2026)
The fishing industry has historically relied on the use of expanded polystyrene (EPS) and, sometimes, on wooden boxes for fish transport. However, these materials pose significant environmental and hygienic challenges, particularly due to the persistence of polystyrene in marine ecosystems and the porosity of wood, which undermines food safety. This study investigates the adoption of polypropylene-based eco-sustainable boxes, assessing the economic viability by a scenario simulation approach applied to a total of six case studies from the Italian fishing fleet. The findings indicate that the transition to polypropylene (PP) eco-boxes improves profitability across all fishing fleets with large scale fisheries (trawling and purse seine fleets) achieving increases in gross profit never below +21%. Smaller or less intensive fleets (longliners) see more modest average gains (in gross profit terms) between of +2.5% over the long-term horizon. So, although initial investments are higher, PP eco-boxes lead to cost savings over time, enhanced profitability and compliance with environmental and food safety standards. Furthermore, these initiatives have the potential to facilitate traceability and valorization of fish products, thereby increasing the overall benefits deriving from the utilization of eco-sustainable boxes. The study concludes that eco-sustainable boxes represent a feasible and beneficial innovation for the Italian fishing sector, with scalability potential across the Mediterranean.

Single mixed refrigerant biomethane liquefaction plant integrated with solar energy: Dynamic simulation for the decarbonization of the heavy road transport sector - Francesco Calise; Francesco Liberato Cappiello; Luca Cimmino; Massimo Dentice d’Accadia; Maria Vicidomini (Journal of Environmental Management, 2024)

The detection of a strong episignature for Chung–Jansen syndrome, partially overlapping with Börjeson–Forssman–Lehmann and White–Kernohan syndromes - Niels Vos; Sadegheh Haghshenas; Liselot van der Laan; Perle K. M. Russel; Kathleen Rooney; Michael A. Levy; Raissa Relator; Jennifer Kerkhof; Haley McConkey; Saskia M. Maas; Lisenka E. L. M. Vissers; Bert B. A. de Vries; et al. (Human Genetics, 2024)
Chung-Jansen syndrome is a neurodevelopmental disorder characterized by intellectual disability, behavioral problems, obesity and dysmorphic features. It is caused by pathogenic variants in the PHIP gene that encodes for the Pleckstrin homology domain-interacting protein, which is part of an epigenetic modifier protein complex. Therefore, we hypothesized that PHIP haploinsufficiency may impact genome-wide DNA methylation (DNAm). We assessed the DNAm profiles of affected individuals with pathogenic and likely pathogenic PHIP variants with Infinium Methylation EPIC arrays and report a specific and sensitive DNAm episignature biomarker for Chung–Jansen syndrome. In addition, we observed similarities between the methylation profile of Chung–Jansen syndrome and that of functionally related and clinically partially overlapping genetic disorders, White–Kernohan syndrome (caused by variants in DDB1 gene) and Börjeson–Forssman–Lehmann syndrome (caused by variants in PHF6 gene). Based on these observations we also proceeded to develop a common episignature biomarker for these disorders. These newly defined episignatures can be used as part of a multiclass episignature classifier for screening of affected individuals with rare disorders and interpretation of genetic variants of unknown clinical significance, and provide further insights into the common molecular pathophysiology of the clinically-related Chung–Jansen, Börjeson–Forssman–Lehmann and White–Kernohan syndromes.